ADVANCED SOLAR ASSISTED DRYING SYSTEMS FOR MARINE AND AGRICULTURAL PRODUCTS (Journal of Mechanical Engineering, 2013)
Solar assisted drying systems are cost effective and suitable for drying of various marine andagricultural products. The way forward for advanced solar assisted drying systems is compact collector design,high efficiency, integrated storage, and long-life systems. Air based solar collectors are not the only availablesystems. Water based collectors can also be used whereby water to air heat exchanger can be used. The hot airfor drying of agricultural produce can be forced to flow in the water to air heat exchanger. The hot water tankacts as heat storage of the solar drying system. Heat pump drying system can be effective use for as part of solarassisted drying systems. Moreover, innovative applications of photovoltaic thermal system for simultaneousproduction of heat and electricity are suitable as standalone applications and totally operated on solar energy.The Solar Energy Research Institute has developed four advanced solar assisted drying system suitable fordrying of various marine and agricultural products namely (a) the solar assisted drying systems with thedouble-pass solar collector with fins (b) solar assisted dehumidification system (c) solar assisted chemical heatpump system and (d) solar assisted heat pump with photovoltaic thermal collectors.DOI: http://dx.doi.org/10.3329/jme.v42i1.15912